In Silico Prediction and Bioactivity Evaluation of Chemical Ingredients Against Influenza A Virus From Isatis tinctoria L - Cai, Chuipu; Xu, Lvjie; Fang, Junfeng; Dai, Zhao; Wu, Qihui; Liu, Xiaoyi; Wang, Qi; Fang, Jiansong; Liu, Ai-Lin; Du, Guan-Hua (Frontiers in Pharmacology, 2021)
Influenza A virus (IAV) is one of the major causes of seasonal endemic diseases and unpredictable periodic pandemics. Due to the high mutation rate and drug resistance, it poses a persistent threat and challenge to public health. Isatis tinctoria L. (Banlangen, BLG), a traditional herbal medicine that widely used in Asian countries, have been reported to possess strong efficacy on respiratory viruses, including IAV. However, its effective anti-IAV components and mechanism of actions (MOAs) are not yet fully elucidated. In this study, we first summarized the chemical components and corresponding contents in BLG according to current available chemical analysis literature. We then presented a network-based in silico framework for identifying potential drug candidates against IAV from BLG. A total of 269 components in BLG were initially screened by drug-likeness and ADME evaluation. After that, network predictive models were built via integration of compound-target networks and influenza virus-host proteins. We highlighted 23 compounds that possess high potential of anti-influenza virus. Through experimental evaluation, there are six compounds, including eupatorin, dinatin, linarin, tryptanthrin, indirubin, and acacetin, exhibited good inhibitory activity against wild-type H1N1 and H3N2. Particularly, they also exert significant effects on drug resistant strain. Finally, we explored the anti-IAV MOAs of BLG and showcased the potential biological pathways by systems pharmacology analysis. In conclusion, this work provides important information of BLG for its usage and development of anti-IAV, and the network-based prediction framework proposed here also offers forceful strategy for in silico identification of novel drug candidates from complex components of herbal medicine.